Clara Happel papers - Happel, Clara, 1889-1945.
Letters to Happel principally from members of the psychoanalytic community in Berlin, Germany, including Felix Boehm, M. Eitingon, Sandor Rado, and Hanns Sachs. Also includes programs from psychoanalytic congresses and meetings.
Psychoanalyst.
In German.
Forms part of: Sigmund Freud collection.
Keywords: Boehm, Felix, -- 1881-1958 -- Correspondence; Eitingon, M. -- 1880-1943 -- Correspondence; Rado, Sandor, -- 1890-1972 -- Correspondence; Sachs, Hanns, -- 1881-1947 -- Correspondence; Psychoanalysis; Psychoanalysis -- Societies, etc; Psychoanalysts -- Germany -- Berlin; Psychoanalysts